2006
DOI: 10.1016/j.ejcts.2006.02.046
|View full text |Cite
|
Sign up to set email alerts
|

‘The electrical spiral of the heart’: its role in the helical continuum.The hypothesis of the anisotropic conducting matrix

Abstract: The study of the dissemination of the electrical impulse throughout the ventricular myocardium, which gave rise to the current theories, was carried out without taking into consideration the complex architecture of the cardiac muscle elucidated by more recent researchers. We propose a novel hypothesis based on the special macroscopic structure of the heart, the anisotropic electrical and mechanical behavior of the myocardium, the characteristics of the intercellular matrix and its very special collagen scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The clinical relevance of these adaptations is unknown. Purkinje conduction is putatively linked to myocardial extracellular matrix ionic composition and myocardial fiber folding [72], which may also be dynamic, again with unknown clinical consequences. Autonomic influences [30, 73, 74] and antiarrhythmic drugs confer further functional Purkinje plasticity.…”
Section: Infrahisian Conduction System and Endocavitary Structuresmentioning
confidence: 99%
“…The clinical relevance of these adaptations is unknown. Purkinje conduction is putatively linked to myocardial extracellular matrix ionic composition and myocardial fiber folding [72], which may also be dynamic, again with unknown clinical consequences. Autonomic influences [30, 73, 74] and antiarrhythmic drugs confer further functional Purkinje plasticity.…”
Section: Infrahisian Conduction System and Endocavitary Structuresmentioning
confidence: 99%
“…Sodium conductance in the DiFrancesco-Nobel model was increased threefold (5) to increase maximum upstroke velocity (‫ץ‬V m/‫ץ‬t) in uncoupled cells from 169 to 380 mV/ms, which is closer to the in vitro value reported by Lu et al (25). Purkinje cell radius was set to 15 m, and intracellular conductivity was set to 1.5 S/m to achieve the conduction velocity (CV) ratio of 4.4 with reference to the myocardium (4), which is within the experimental range (11). Figure 1B shows ventricular excitation by the PS during normal sinus rhythm.…”
Section: Governing Equations and 3d Modelmentioning
confidence: 92%
“…Without modifications to published parameters in both models, the ratio of PS and longitudinal myocardial conduction velocities (Θ PS /Θ myo ) was slightly greater than 1, falling short of accepted values, which range from 2 to 10, depending on species [9]. Model parameters were adjusted to better reflect physiological behaviour:…”
Section: B Physiological Modelmentioning
confidence: 99%
“…In vivo studies have demonstrated inter-species differences in Purkinje endpoint penetration depth [9]. Thus, the effect of defibrillation-strength shocks was assessed for PS structures with surface-coupled fibres, midwall-penetrating fibres (onethird and two-thirds), and fully-penetrating fibres, which nearly reach the epicardium.…”
Section: Defibrillation Shocksmentioning
confidence: 99%